Analytical model for transient coupled consolidation and contaminant transport in landfill liner system. (October 2021) - Yan, Huaxiang; Xie, Haijian; Wu, Jiawei; Ding, Hao; Qiu, Zhanhong; Sun, Zhilin
Abstract: Analytical model for transient contaminant transport in clay barrier under combined effects of diffusion, adsorption and consolidation processes are developed. The generalized integral transform technique (GITT) is adopted to successfully derive the analytical solutions. The proposed analytical model is validated by experimental results. The analytical models are applied to develop an understanding of how contaminant migration is governed by a combination of the consolidation and diffusion processes. The effects of effective diffusivity, hydraulic conductivity, void ratio and adsorption coefficient are investigated. It was demonstrated that the consolidation model with large displacement induces the shortest breakthrough time compared to the consolidation model with small displacement and no consolidation model. The settlement, advection and spatial variation of the void ratio induced by large displacement model are attributable to an earlier breakthrough of contaminant. The advection flux induced by consolidation is an important component to develop an accurate assessment of contaminant migration in deforming clay barrier. The contribution of advection process to total contaminant flux can reach 29%. The results indicate that coupled consolidation and contaminant migration models are necessary to design a conservative clay barrier. The proposed analytical model also provides modelling benchmarks to examine the accuracy of alternative multi-physics numerical models.